Crystal structure of ethyl 6-bromo-2-[(E)2-phenylethenyl]quinoline-4-carboxylate. (February 2015) - Kumar, T. O. Shrungesh; Naveen, S.; Kumara, M. N.; Mahadevan, K. M.; Lokanath, N. K.
No abstract available